2019
DOI: 10.1016/j.sleep.2019.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Using big data to explore worldwide trends in objective sleep in the transition to adulthood

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 36 publications
6
32
1
Order By: Relevance
“…Our results on gender differences in sleep durations were also unique. In contrast to women in other countries 1 , 3 , 4 , 36 , Japanese women slept 30 min shorter than similarly aged men on average. According to the questionnaire-based survey conducted by the Organization for Economic Co-operation and Development (OECD) 48 , women tend to sleep longer than men in almost all OECD countries, with just a few exceptions (Japan, India, Mexico, Estonia), and among these exceptions, the Japanese results were an extreme case.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Our results on gender differences in sleep durations were also unique. In contrast to women in other countries 1 , 3 , 4 , 36 , Japanese women slept 30 min shorter than similarly aged men on average. According to the questionnaire-based survey conducted by the Organization for Economic Co-operation and Development (OECD) 48 , women tend to sleep longer than men in almost all OECD countries, with just a few exceptions (Japan, India, Mexico, Estonia), and among these exceptions, the Japanese results were an extreme case.…”
Section: Discussioncontrasting
confidence: 57%
“…We found a remarkable time shift toward earlier bedtimes and earlier wake times with increasing age between 20 and 89 years, thus indicating a phase advance of sleep–wake cycles with aging. A variety of population-based studies have consistently reported a similar result using both subjective 12 , 35 and objective assessments 3 , 4 , 36 , as well as cross-country meta-analysis 1 . Consistent reports of a systematic phase advance across different population groups suggest the presence of an underlying endogenous physiological mechanism; alterations in the output of the human circadian pacemaker may cause the systematic phase advance, as discussed in previous studies 42 , 43 .…”
Section: Discussionmentioning
confidence: 77%
“…the mid‐point of sleep on free days; Zavada et al, 2005). During adolescent development (10–20 years), the mid‐point of sleep dramatically drifts later and begins to reverse again during the mid‐20s (Kuula et al, 2019). Numerous studies have shown an association between eveningness/ a later chronotype/ later circadian timing and depression symptoms or a depressive disorder (Bauducco et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…8 Screen time may replace activities and routines that are relaxing and that promote more adequate sleep hygiene, 9 defined as a variety of different practices and habits that are necessary to have better sleep quality and full daytime alertness. 10 Additionally, evidence suggests that other environmental aspects such as the region of residence [11][12][13] or culture 14 are associated with sleep patterns. A previous study 15 showed that children between 2 and 9 years from Mediterranean countries, including Spain, and Eastern countries, have shorter nocturnal sleep duration compared with Northern countries.…”
Section: Backg Rou N Dmentioning
confidence: 99%